Innovation on Street Food Products (Instant Porridge and Cookies) Based on Fortified Patin Fish Protein Concentrate with Red Palm Oil and Encaptulated Oil Fish - Dewita Dewita; Syahrul Syahrul; Desmelati Desmelati; Suardi Lukman (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
This research aimed to establish innovation on street food (instant porridge and cookies)from Patin Fish Protein Concentrate fortified by blending red palm oil and encaptulated patinfish’s oil. The Encaptulation was conducted by blending of red palm oil and patin fish’s oil usingspray dryer. The blending was consisted of three combinations namely 50 : 50 (A1), 40 : 60 (A2)and 60 : 40 (A3) for ratio between red palm oil and patin fish’s oil. The best combination’s resultswas fortified into street food (instant porridge and cookies). The blending was tested by measureyield, fat and fatty acid profile. Moreover, organoleptics and proximate tests were carrie out for thebest treatment of blending in instant porridge and cookies. The results show that encaptulatedyield reached 55 % that rise from A1 treatment as the best treatment with fat content of 17.26%.Profile of unsaturated fatty acid especially fatty acid omega 9 from blending fish oil and palm oilwas 59.29%. The number of fatty acid omega 9 was higher than saturated fatty acid which was18.56%. Furthermore, based on organoleptic tests of instant porridge and cookies using under fiveyear children respondents, it was proven that 93% of children was like the products. Proximate analysis of instant porridge revealed that protein content was 11.04 %, water content was 5.03%,fat content was 1.92 % and ash was 0.64 %. However, proximate analysis showed that cookiesowned protein of 9.11%, fat of 17.03% , water content was 3.93% and ash of 1.38%.Keywords : Encaptulated fish, street food, patin fish protein concentrate, palm oil